2012
DOI: 10.1371/journal.ppat.1002485
|View full text |Cite
|
Sign up to set email alerts
|

The bZIP Transcription Factor Rca1p Is a Central Regulator of a Novel CO2 Sensing Pathway in Yeast

Abstract: Like many organisms the fungal pathogen Candida albicans senses changes in the environmental CO2 concentration. This response involves two major proteins: adenylyl cyclase and carbonic anhydrase (CA). Here, we demonstrate that CA expression is tightly controlled by the availability of CO2 and identify the bZIP transcription factor Rca1p as the first CO2 regulator of CA expression in yeast. We show that Rca1p upregulates CA expression during contact with mammalian phagocytes and demonstrate that serine 124 is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 44 publications
10
68
2
Order By: Relevance
“…Consistent with the study published by Cottier et al (16), we found that carbonic anhydrase (NCE103) was downregulated upon RCA1 deletion. However, several discrepancies were found when comparing our results with those of Cottier et al (16). First, Cottier et al (16) stated that the rca1 mutant was unable to form hyphae, while in our hands, it produced hyphae even under yeast-inducing conditions.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Consistent with the study published by Cottier et al (16), we found that carbonic anhydrase (NCE103) was downregulated upon RCA1 deletion. However, several discrepancies were found when comparing our results with those of Cottier et al (16). First, Cottier et al (16) stated that the rca1 mutant was unable to form hyphae, while in our hands, it produced hyphae even under yeast-inducing conditions.…”
Section: Discussioncontrasting
confidence: 78%
“…We focused our investigations on the orf19.6102 mutant, since it exhibited resistance to FLC and CAS and thus was likely to contribute to understanding of crossresistance to drugs with different modes of action. Interestingly, while the present work was ongoing, this TF was identified as the regulator of carbonic anhydrase expression (16) and was consequently named RCA1 (for regulator of carbonic anhydrase). To characterize the function of this TF in addition to its role in CO 2 sensing, and to understand how it modulates antifungal susceptibility, we performed strand-specific RNAseq analyses to identify RCA1-regulated genes by comparing the transcriptomes of RCA1 mutant and revertant strains (raw RNAseq results are available in Table S5 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have shown that elevated levels of CO 2 , as found in exhaled breath, can trigger a morphological switch in C. albicans and that this is important for infection and virulence (Cottier et al, 2012;Hall et al, 2010;Klengel et al, 2005). Our preliminary work shows that elevated levels of CO 2 also promote biofilm formation upon VP surfaces (our unpublished results) leading to the possibility that this is a factor that may influence colonization rates in patients fitted with prosthetic devices following larynx removal.…”
Section: Formation and Structure Of Candida Biofilmssupporting
confidence: 51%
“…HCO 3 2 then regulates hyphal morphogenesis through its activation of the adenylyl cyclase Cyr1 and, subsequently, the cAMP-PKA pathway (Klengel et al 2005). HCO 3 2 also signals independently of Cyr1 to regulate levels of carbonic anhydrase (Cottier et al 2012) and promote hyphal development and cell-fate transition (Du et al 2012a). Stabilization of Ume6 by CO 2 is likely mediated through a Cyr1-independent pathway.…”
Section: Environmental Regulation Of Hyphal Morphogenesis Sensing Nutmentioning
confidence: 99%